Por uma abordagem semântica do paradoxo : o quadrado argumentativo paradoxal - Borges, João Henrique Casara (2015)
The following paper intends to analyze the paradox, through the Theory of the Semantic Blocks, considering, mostly, the relations that occurs inside the four-sided figure that demonstrate how the meanings get along. In order to do that, will be studied the conceptions arising from the referred theory, as well as its conventional roots and theories from another theorists. Along the revision of the pertinent literature will be studies ideas from Ferdinand de Saussure, especially the ones about relation and linguistic values, because they are significant important to understand the linguistic meaning of any terms in the language. Another idea that will be developed at the following paper is the empty sign, studied by Benveniste, which will be explained and will be the object for new considerations, in order to study the presence of an emptiness inside every word. Also during the study of the literature, the ideas of meaning understood only by the linguistic relations among words will be object of thoughts. In order to do that, the ideas of Oswald Ducrot and Marion Carel will be very important, especially the linguistic orientation, linguistic relations, because they will demonstrate how the meaning is constructed. Other notions of those two theoretical authors are the idea of semantic block and argumentative four-sided figure. The paradox, according to the semantics, will be studied considering the ideas of Carel, Ducrot and Borges (2011), aiming its application in the argumentative figure. Specifically, the observation of the paradox in the figure can demonstrate how the normative and transgressive relations occurs. There were select a song and an advertisement to demonstrate those kind of relations, by using a methodology that focus in the particular cases. At the end, the results will be shown and the final considerations will be constructed, based on the premise of analyzing the paradox in the argumentative four-sized figure.